The use of physiotherapy and the role of physical exercise in cancer - Chłystek, Joanna; Bielejewska, Marta; Dudzik, Katarzyna; Traczyk, Anna; Łakomski, Mateusz (Journal of Education, Health and Sport, 2018)
After the application of oncological treatment, it is important to implement physiotherapy, the basic component of which is kinesitherapy. It is not always possible to implement the rehabilitation procedure early enough, so you should take into account the time spent in bed before starting the exercise and assess the physical performance. Research shows that the best benefits are achieved by activity undertaken 5 days a week, lasting a minimum of 30 minutes, with moderate intensity. Physical activity in the advanced stage of cancer can positively affect the physical and mental well-being, the level of fatigue experienced, and even increase the independence of the patient. The aim of using palliative procedures is primarily to control persistent and severe pain, prevent the negative effects of immobilization and provide psychological support for the patient and family members. Numerous studies also indicate that exercise can also help to reduce the risk of certain forms of cancer, and increase the survival time from the moment of diagnosis. Researchers also confirming a favorable correlation between physical effort and the quality of life of patients suffering from cancer.